ANALISIS PENDEKATAN PERILAKU TERHADAP MOTIVASI ANGGOTA SANGGAR SENI BUDAYA BESAPEN KABUPATEN TULANG BAWANG - Filiae Marry (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
Lampung cultural erosion is caused by a lack of initiative in the use of culture, the notion thatculture ancient and outdated. One way in preserving the culture of Lampung is to introduce theculture of the young generation, especially for the younger generation in the area of Tulang Bawang.The phenomenon of a traditional studio making of Culture and Tourism Govenrment ofTulang Bawang participate with better behavioral approach to the studio. This is how the traditionalstudio is motivated to be able to survive in the midst of the loss of cultural Lampung – TulangBawang among the younger generation.